The institute for public-private partnerships in the power industry: content and form - R. A. Burganov; A. G. Yarullina (Известия высших учебных заведений: Проблемы энергетики)
The work is devoted to the definition of «public-private partnership» in the energy sector in view of the multiplicity and ambiguity of interpretation of this concept in the scientific community. This article discusses the main approaches of foreign and domestic researchers in the area of interpretation of this process, as a public-private partnership. Based on the analysis of the definitions of public-private partnership and allocated to the specific characteristics of public-private partnership in the energy sector we have given the definition of public-private partnership in the energy sector. The article also discusses the possible forms of cooperation between the state and the private sector, and identified effective form of implementing PPP projects in the energy sphere. In the conditions, the need to balance the interests of the state and private businesses, effective form of interaction partners in the implementation of PPP projects in the energy sphere can become life cycle contracts.